2015
DOI: 10.1371/journal.pone.0117146
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine for Neck Pain and Low Back Pain: A Systematic Review and Meta-Analysis

Abstract: BackgroundNeck pain (NP) and low back pain (LBP) are common symptoms bothering people in daily life. Traditional Chinese medicine (TCM) has been used to treat various symptoms and diseases in China and has been demonstrated to be effective. The objective of the present study was to review and analyze the existing data about pain and disability in TCM treatments for NP and LBP.MethodsStudies were identified by a comprehensive search of databases, such as MEDLINE, EMBASE, and Cochrane Library, up to September 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
151
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(159 citation statements)
references
References 93 publications
(162 reference statements)
6
151
0
2
Order By: Relevance
“…Electroacupuncture proved to significantly reduce neck pain after therapy and at 3 months post-therapy (Cameron et al, 2011;Sahin et al, 2010) as well as significantly reducing restriction in daily activities after the treatment and at the 3-month and 6-month follow-up (Cameron et al, 2011). Acupuncture and acupressure also could be efficacious in neck pain and the related disability (Yuan et al, 2015). An overview of Cochrane reviews concluded that acupuncture is effective in reducing some types of pain but not all of them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electroacupuncture proved to significantly reduce neck pain after therapy and at 3 months post-therapy (Cameron et al, 2011;Sahin et al, 2010) as well as significantly reducing restriction in daily activities after the treatment and at the 3-month and 6-month follow-up (Cameron et al, 2011). Acupuncture and acupressure also could be efficacious in neck pain and the related disability (Yuan et al, 2015). An overview of Cochrane reviews concluded that acupuncture is effective in reducing some types of pain but not all of them.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment modalities include also therapies based on acupuncture points. Acupuncture is accepted and recommended for the treatment of neck pain (Nunes, Moita, 2015;Yuan et al, 2015;Liang et al, 2010;Witt et al, 2006;Vas et al, 2006;He et al, 2004;Irnich et al, 2001). Acupressure reduces neck pain intensity, neck stiffness and stress level (Yuan et al, 2015;Matsubara et al, 2011;Yip, Tse, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…(3) The diseases that may be treated in the Chinese sphere is wide, highlighting the rheumatism, the headaches, chronic fatigue, back and cervical region pains, sciatic, digesting problems, asthma, metabolic disorders, breast angina, hypertension, immunological system deficiencies, according to Hong Kong's population that uses it. (4) In the literature, it is possible to find researches about treatments of neck pains, low back pains, headaches, increase of blood circulation in the treated area, improvement in mother's breastfeeding by the better breast engorgement, better hormonal control in hyperthyroidism, showing always the best results in comparison to other control groups.…”
Section: Introductionmentioning
confidence: 99%
“…The areas that show energetic instability show, besides the hyperemia, a deeper pigmentation that, according to the TCM, indicate the stagnation of vital fluids (Xue -blood) e energy (Qi) from the meridians, the so called channels of body energy. (4) The patient doesn't feel pain during or after the treatment, but in some cases a bruise appears over the area, the pigmentation fades in a few days without leaving traces. (13) However, in the western culture this pigmentation may be misunderstood, that's what an Italian study highlighted (14) , about the forensic implication of the technique, because of the pigmentation that lasts on the skin for a few days, which may be considered a bodily injury.…”
Section: Introductionmentioning
confidence: 99%
“…ELS is a form of systems theory developed in the West by Dr. Maurice Mussat that incorporates knowledge of ancient texts and a contemporary understanding of mathematics and biology. 7,8 Scientific reports of the implementation of acupuncture for clinical conditions include back pain, 9 migraine, 10 recovery from stroke, 11 anxiety and depression, 12 insomnia, 13 schizophrenia, 14 and gynecologic complications. 15 The efficacy of acupuncture for the treatment of conditions that involve the immune system has been reported for allergies, 16 pain relief, 17 arthritis, 17 allergic rhinitis, 18 asthma, 19 and inflammation.…”
Section: Introductionmentioning
confidence: 99%